Motivation : theory, research, and applications - Petri, Herbet L.; Govern, John M. (Belmont, CA : Wadsworth/Cengage Learning, 2013)
With its signature focus on evolutionary psychology, this edition reflects the latest developments from the field in its thorough coverage of the biological, behavioral, and cognitive explanations for human motivation. The book clearly presents the advantages and drawbacks to each of these explanations, allowing readers to draw their own conclusions. The authors help readers understand the processes that activate their behavior by drawing examples from such relevant topics as sleep, stress, eating disorders, helping behavior, emotion, and more. Extremely reader friendly, the book includes vivid graphic illustrations that offer additional insight into key concepts.
Part 1. Overview -- Part 2. Physiological Mechanisms of Motivation -- Part 3. The Behavioral Approaches: Learning, Incentives, and Hedonism -- Part 4. Cognitive Approaches to Motivation -- Part 5. Emotion and Motivation -- Part 6. End view
Includes bibliographical references and index.
Keywords: MOTIVATION -- PSYCHOLOGY